Intermolecular C(sp3)−H Amination Promoted by Internal Oxidants: Synthesis of Trifluoroacetylated Hydrazones. (27th November 2018) - Zhu, Chuanle; Zeng, Hao; Chen, Fulin; Yang, Zhiyi; Cai, Yingying; Jiang, Huanfeng
Abstract: An intermolecular C(sp 3 )−H amination reaction is reported that is promoted by internal oxidants and occurs via a C=N bond formation step. This intermolecular C(sp 3 )−H amination reaction of trifluoromethyl ketones and aryldiazonium tetrafluoroborates affords various valuable trifluoroacetylated hydrazones in high yields with excellent E / Z selectivities. The salient features of this reaction type is that it is free of metal, catalyst, directing groups, and azides, and that it can be carried out under mild conditions, is operationally simple and efficient, gram‐scalable, and it tolerates various functional groups. Remarkably, an ectoparasites‐controlling agent was smoothly synthesized on a gram scale using our method. Aryldiazonium tetrafluoroborates served as the aminating reagents as well as an internal oxidant. Abstract : Insider‐Job : Eine intermolekulare C(sp 3 )‐H‐Aminierung wird vorgestellt, die durch interne Oxidantien vermittelt wird und unter milden Bedingungen abläuft. Trifluoracetylierte Hydrazone werden unter C=N‐Bindungsbildung erzeugt und in nützliche trifluormethylierte Verbindungen umgewandelt.